2019
DOI: 10.1101/608646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Network science inspires novel tree shape statistics

Abstract: 1 Abstract 1The shape of phylogenetic trees can be used to gain evolutionary insights. A tree's shape specifies 2 the connectivity of a tree, while its branch lengths reflect either the time or genetic distance 3 between branching events; well-known measures of tree shape include the Colless and Sackin 4 imbalance, which describe the asymmetry of a tree. In other contexts, network science has 5 become an important paradigm for describing structural features of networks and using them 6 to understand complex sy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…HIV and influenza virus trees The HIV trees were described and analyzed previously (Chindelevitch, 2019). Briefly, HIV-1 sequence data from three studies were used.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…HIV and influenza virus trees The HIV trees were described and analyzed previously (Chindelevitch, 2019). Briefly, HIV-1 sequence data from three studies were used.…”
Section: Datamentioning
confidence: 99%
“…These datasets reflect a diverse set of spatial scales and epidemiological contexts. Phylogenetic reconstruction was described in (Chindelevitch, 2019); briefly, trees were reconstructed using RAxML (Stamatakis, 2014), which is a maximum likelihood method, under a general time-reversible (GTR) model of nucleotide substitution. We use a GTRCAT model for rate variation among sites.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a growing interest in how network science can provide novel ways to characterize the shape of phylogenetic trees (Chindelevitch et al, 2019). We found that the shape of a phylogeny, and more specifically its stem-to-tip asymmetry increased-indicating more frequent terminal branching events (Lewitus and Morlon, 2016)-as the size of the refugia decreased compared to present, even more so if expansions occurred long ago.…”
Section: Phylogenetic Diversity Keeps Track Of (More) Ancient Habitat Changesmentioning
confidence: 82%
“…first, fifth and sixth tree in Table 3. diameter (a) [15] maximal distance of two vertices diam(T ) := max i,j∈V (T )…”
Section: Normalizing Balance Indicesmentioning
confidence: 99%